Coevolution of Cyclin Pcl5 and Its Substrate Gcn4 - Gildor, Tsvia (American Society for Microbiology, 2005)
Gcn4, a transcription factor that plays a key role in the response of Saccharomyces cerevisiae to amino acid starvation, is regulated at both the levels of translation and of protein stability. Regulated degradation of Gcn4 depends on its phosphorylation by the cyclin-dependent kinase Pho85, in conjunction with the cyclin Pcl5. The pathogenic yeast Candida albicans contains a functional homolog of Gcn4, which is involved in amino acid metabolism, as well as in the regulation of filamentous growth in response to starvation. Here, we show that C. albicans Gcn4 (CaGcn4) is rapidly degraded and that this degradation depends on a Pho85 cyclin homolog, CaPcl5. The regulatory loop that includes Gcn4 and Pcl5 is conserved in C. albicans: like in S. cerevisiae, CaPcl5 is transcriptionally induced by CaGcn4 and is required for CaGcn4 degradation. However, the proteins have coevolved so that there is no cross-recognition between the proteins from the two species: phosphorylation-dependent degradation of CaGcn4 occurs only in the presence of CaPcl5, and S. cerevisiae Gcn4 (ScGcn4) requires ScPcl5 for its degradation. Phenotypic analysis of the Capcl5 mutant indicates that CaPcl5 also modulates the filamentous response of C. albicans in amino acid-rich media.